Tsunamiites : features and implications - Shiki, T. (Elsevier, 2008)
This book is an overview of the state-of-the art developments in sedimentology of tsunami-induced and tsunami-affected deposits, namely tsunamiites. It also points out any problems that need additional investigation, as well as providing insight into the direction of future tsunamiite researches. Important characteristics of tsunami wave and tsunami currents are explained. There are reports on the sediments generated by recent tsunami including the 2004 Indian Ocean tsunami presented. Tsunamiites induced by other seismic activities, a submarine slump and a volcanic eruption are investigated as well. Several contributions in this book present new ideas concerning the characteristic sedimentary records of tsunamis and provide the criteria for recognizing features of various tsunamiites. The importance of studies of bedforms of tsunamiites from various environments is emphasized. New information is provided on tsunami-derived boulder deposits. The significance of studies on tsunamiites in the archeological and geological past is also illustrated in this book. For example, the Mediterranean homogenites, and the K/T boundary meteorite impact-induced tsunamiites have been investigated from new aspects. * Provides a comprehensive overview of developments in tsunamiites * Investigates future trends and development needs * Cutting edge research articles from leading experts aimed at researchers and scientists.